2011
DOI: 10.1016/j.pharmthera.2011.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of termination and prevention of atrial fibrillation by drug therapy

Abstract: Atrial fibrillation (AF) is a disorder of the rhythm of electrical activation of the cardiac atria. It is the most common cardiac arrhythmia, has multiple aetiologies, and increases the risk of death from stroke. Pharmacological therapy is the mainstay of treatment for AF, but currently available anti-arrhythmic drugs have limited efficacy and safety. An improved understanding of how antiarrhythmic drugs affect the electrophysiological mechanisms of AF initiation and maintenance, in the setting of the differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 235 publications
(262 reference statements)
3
34
0
Order By: Relevance
“…39,40 This may explain experimental data showing that the inhibition of I Kur can actually promote the induction of AF. 41 Our simulation results may also provide mechanistic insights into the clinically observed superiority of amiodarone over other drugs used for AF treatment, 15,24,36 as amiodarone uniquely reduces the likelihood of both re-entry and wave breaks (Table 3). …”
Section: Discussionmentioning
confidence: 94%
“…39,40 This may explain experimental data showing that the inhibition of I Kur can actually promote the induction of AF. 41 Our simulation results may also provide mechanistic insights into the clinically observed superiority of amiodarone over other drugs used for AF treatment, 15,24,36 as amiodarone uniquely reduces the likelihood of both re-entry and wave breaks (Table 3). …”
Section: Discussionmentioning
confidence: 94%
“…22 Unfortunately, as AF progresses electric remodeling of the atria render it is progressively more conducive to perpetuation of re-entry, such that the antiarrhythmic dose required to achieve sufficient action potential duration prolongation in the atria can result in proarrhythmia in the ventricles.…”
Section: Antiarrhythmic Medication For Re-entrant Rhythmsmentioning
confidence: 99%
“…The potential effectiveness of pharmacological treatment of AF was investigated in Colman et al [45]. It was demonstrated that potassium channel blockers have both pro-and anti-arrhythmic effects, compared to the multi-channel blocker amiodarone which demonstrated only anti-arrhythmic effects, consistent with experimental studies [51].…”
Section: Termination Of Atrial Fibrillationmentioning
confidence: 82%